Peningkatan Toleransi Siswa SMA sebagai Fungsi dari Bimbingan Kelompok Teknik Permainan Monopoli - Isnaeni Budiarti; Wahyu Nanda Eka Saputra; Nur Handayani (Jurnal Psikoedukasi dan Konseling, 2022)
Abstract: Tolerance is the attitude of respecting, accepting and appreciating the world's cultural diversity. This study aims to determine the implementation of the monopoly game technique group guidance in increasing the tolerance of high school students. The type of research used is Guidance and Counseling Action Research. The subjects of this study were 10 students in a low tolerance category. The treatment used was the simulation game. Simulation game is a game technique in learning inspired from real life situation. The study was carried out in pre-cycle, cycle I, and cycle II stages. The analysis of the data used was descriptive quantitative implemented in providing a detailed explanation of quantitative data by comparing the results of the questionnaire scores before and after the action using statistics. Based on the results of the study, the pre-cycle scoreas 1,089 with an average of 108.9, the score of the first cycle was 1,148 obtained with an average of 114.8, and in the second cycle, a score of 1,286 was obtained with an average of 128.6. These results indicate an increase in the score for each student. Based on the results of the discussion, it can be seen that the implementation of the monopoly game technique group guidance in increasing the tolerance.